Portal E-Sertifikat dengan QR Code Menggunakan PHP dan MYSQL - Muhhammad Rifal Hidayat; Deddy Gusman; Hanantatur Adeswastoto (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The increasing globalization of integrated system communication technology makes the world seem to be borderless, especially with the increasingly widespread use of the internet (interconnection network). One of the most developed cyber activities related to the use of the internet is electronic business transactions, the definition of Electronic Transactions is legal acts carried out with using computers, computer networks and other electronic media. Meanwhile, an electronic system is a series of electronic devices and procedures that function to prepare, collect, process, analyze, store, display, announce, transmit and/or disseminate electronics. Currently, the need for information in activities to get certificates such as seminars, training, webinars and others is sought after by not only students but also the general public. This is due to the large number of companies that require a certificate of activity when applying for a job and graduation in Higher Education. In handling the process of processing data activities which includes member registration, activity planning, certificate printing to report printing until now is still running traditionally in the sense that certificate printing is carried out collectively so that data processing often occurs loss and damage to data on activities that have been carried out and the length of time for printing certificates, this is because certificate printing is carried out 1 (one) week after the activity is carried out.